Analisis Pengaruh Modal Kerja, Lama Usaha dan Jam Kerja terhadap Pendapatan Pedagang Kaki Lima di Kawasan Darmo Permai Surabaya Tahun 2021 - Soemardianto, Kevin Dion (Economie: Jurnal Ilmu Ekonomi, 2023)
The purpose of these study to " The Analysis of Working Capital, Length of Business and Office Hour to Income of Street Vendors in Darmo Permai Surabaya in 2021". These study used Cross Section data with 61 samples were tested on multiple linear regression method to showed an increase of generated by street vendors based on working hours and the length of business that the street vendors have occupied. Simultaneously there was an impact on increasing the income of street vendors on the hours worked and the length of the business occupied, while partially only working hours will have a positive impact on the income of street vendors at the Darmo Permai Location Surabaya 2021.